Effect of arbuscular mycorrhizae on the growth of Cinchona officinalis L. (Rubiaceae) in nursery - Fernandez Zarate, Franklin Hitler (2024)
Cinchona officinalis, commonly called cascarilla or quina, has medicinal value; and is on Peru’s national coat of arms representing its plant wealth (flora), however, it is threatened by anthropogenic activities. This study aimed to determine the effect of the commercial product Myco Grow® on the growth of C. officinalis in nursery. A randomized design was used with two treatments, one with Myco Grow® application (WM) and the other without incorporating this commercial product (NM). Each treatment had three replicates consisting of 30 plants each. Monthly evaluations were performed, during which the number of dead plants, plant height, and plant diameter were recorded. Additionally, at the end of the study, the anhydrous weight of leaves, stems, and roots; leaf area; mycorrhizal frequency; mycorrhizal colonization index; and the length of extra-radicular mycelia were determined. The WM treatment achieved 36.6% lower mortality, 38.01% greater height, and 48.52% greater diameter than the NM treatment. Additionally, inoculation with arbuscular mycorrhizae (AM) improved the anhydrous weights of the leaves, stems, roots, and leaf area by 84.31%, 84.28%, 70.85%, and 76.91%, respectively. Regarding the three fungal variables analyzed for the WM treatment; mycorrhizal frequency was 87%, AM application led to a mycorrhizal intensity of 7.7% and an extra-radicular mycelium length of 90.3 cm. This study confirmed that AM positively influences the growth of C. officinalis in the nursery and can be used to sustainably produce this species on a large scale.